Estimation of financial stability of enterprises of the building industry in the period of 2012-2017 - Pomazunovs`ka, T.; Tsyfra, T. (Ways to Improve Construction Efficiency, 2019)
The article investigates the financial stability of construction industry enterprises. The author concludes about the current crisis situation, analyzing the trends over the past 5 years. To stabilize and boost the economy, you need to increase profits.